Investigating Sino-Africa relations : exploring investment and governance regimes in the Sino-Ugandan oil relations - Swilling, Ranen Annecke (Stellenbosch : Stellenbosch University, 2019)
Thesis (MPhil)--Stellenbosch University, 2019.